The pulmonary artery wedge pressure response to sustained exercise is time-variant in healthy adults. Issue 6 (13th January 2016) - Wright, Stephen P; Esfandiari, Sam; Gray, Taylor; Fuchs, Felipe C; Chelvanathan, Anjala; Chan, William; Sasson, Zion; Granton, John T; Goodman, Jack M; Mak, Susanna
Abstract : Objectives: The clinical and prognostic significance of 'exaggerated' elevations in pulmonary artery wedge pressure (PAWP) during symptom-limited exercise testing is increasingly recognised. However, the paucity of normative data makes the identification of abnormal responses challenging. Our objectives was to describe haemodynamic responses that reflect normal adaptation to submaximal exercise in a group of community-dwelling, older, non-dyspnoeic adults. Methods: Twenty-eight healthy volunteers (16 men/12 women; 55±6 years) were studied during rest and two consecutive stages of cycle ergometry, at targeted heart rates of 100 bpm (light exercise) and 120 bpm (moderate exercise). Right-heart catheterisation was performed to measure pulmonary artery pressures, both early (2 min) and after sustained (7 min) exercise at each intensity. Results: End-expiratory PAWP at baseline was 11±3 mm Hg and increased to 22±5 mm Hg at early-light exercise (p<0.01). At sustained-light exercise, PAWP declined to 17±5 mm Hg, remaining elevated versus baseline (p<0.01). PAWP increased again at early-moderate exercise to 20±6 mm Hg but did not exceed the values observed at early-light exercise, and declined further to 15±5 mm Hg at sustained-moderate exercise (p<0.01 vs baseline). When analysed at 30 s intervals, mean and diastolic pulmonary artery pressures peaked at 180 (IQR=30) s and 130 (IQR=90) s, respectively, and both declined significantly by 420 (IQR=30) s (both p<0.01) of light exercise. Similar temporal patterns were observed at moderate exercise. Conclusions: The range of PAWP responses to submaximal exercise is broad in health, but also time-variant. PAWP may routinely exceed 20 mm Hg early in exercise. Initial increases in PAWP and mean pulmonary artery pressures do not necessarily reflect abnormal cardiopulmonary physiology, as pressures may normalise within a period of minutes.